PERBEDAAN MODEL PEMBELAJARAN KOOPERATIF STAD DAN KOOPERATIF TIPE JIGSAW PADA MATA KULIAH KOMUNIKASI DALAM PRAKTEK KEBIDANAN TERHADAP PRESTASI BELAJAR MAHASISWA - mah, rokhamah; Adelia, Donna Dwinita (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2024)
Cooperative learning has several models including, JIGSAW, TGT and simulation. Communication courses in midwifery practice are courses that discuss more material so that if the lecture model is used, it can quickly cause boredom in students, resulting in decreased performance. To improve this achievement, researchers tried to use the STAD and Jigsaw learning methods. The aim of this research is to determine the differences between the STAD and Jigsaw Cooperative learning models on student achievement in communication courses in midwifery practice. The population in this study were students at the Wira Husada Nusantara Malang Health Polytechnic, midwifery study program, semester 4. The sample in this study was students from classes A and B. Data were analyzed using an unpaired t-test. The results of this research show that there is an influence of the application of the STAD learning model on student achievement, this is shown by the value of t = 19.01 t table 2.02 and seen from the jigsaw cooperative learning, there is an influence of the jigsaw learning model on student achievement, this is shown by the value tcount = 21.19 t table 2.02. From these two learning models, it can be seen that both of them can increase students' knowledge as seen from the post-test scores which are getting better compared to the pre-test scores and if seen from the calculated t value which is greater than the t table value. Based on this, it can be concluded that the calculated t value of the Jigsaw type learning model is higher compared to the STAD type learning model in communication courses in midwifery practice on student learning achievement